Psychiatric manifestations in orthopedic patients on Celecoxib therapy - Arumugam, Manohar; Md. Zain, Azhar (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2010)
Introduction: The Cyclooxygenase-2 (COX-2) enzyme is responsible for the synthesis of prostaglandin which is responsible for inflammation and pain. Celecoxib a cyclooxygenase-2 inhibitor was first used as a non-steroidal anti-inflammatory drug in 1999. Celecoxib is as effective as NSAJDs but causes less ulceration of the gastrointestinal tract, hence it is commonly used. It has been widely used in patients with osteoarthritis and rheumatoid arthritis. We present 3 cases of temporary psychiatric disorders associated with consumption of celecoxib, two of the patients presented with auditory hallucinations while one was diagnosed to be having depression. None had pre-existing psychiatric disorders or consumed alcohol or substance of abuse. All 3 patients recovered from their temporary psychiatric disorders after stopping celecoxib. Discussion: It is important to be aware of the psychiatric side effects when prescribing the drug for prolonged periods.